Развитие рефлексов германского /ē1/ в праанглийских диалектах - Армалите, О. (Kalbotyra, 1976)
One of the earliest Pr OE changes resulting in dialect differentiation was narrowing of the reflexes of Gmc. /ē1/. Pr OE split into West-Saxon, which retained Pr OE /ǣ1/, and non-West-Saxon dialects, where Pr OE /ǣ1/ merged with /ē/ (< Gmc. /ē2/). After the emergence of the new phoneme /ā/ (< Gmc. /ai/) in Pr OE, a new opposition of oral vowels was established. Originally the opposition /ǣ1/-/ā/ was based on labialization. It was isolated in the system where the vowels /ī, ē/ were opposed to /ū, ō/ as front unrounded v. back rounded. The isolated opposition bad to be either better integrated into the system or eliminated. The first of these possibilities was realized in the West-Saxon dialect where eventually /ǣ1/ came to be opposed to /ā/ as front unrounded to back rounded. In non-West-Saxon dialects the opposition /æ̌1/-/ā/ was eliminated by way of the merger of /ǣ1/ with /ē/.